Adequacy of the Global Financial Safety Net. (Policy Papers; Policy Paper ;, 2016)
The Global Financial Safety Net (GFSN) is comprised mainly of countries' own reserves and external public sources of insurance and financing. The main external official arrangements are central bank bilateral swap arrangements (BSAs), regional financial arrangements (RFAs), and the Fund. The safety net seeks to provide countries with insurance against crises, financing when shocks hit, and incentives for sound macroeconomic policies.